A longitudinal assessment of nicotine dependence, mental health, and attempts to quit Smoking: Evidence from waves 1–4 of the Population Assessment of Tobacco and Health (PATH) study. (April 2021) - Snell, Morgan; Harless, David; Shin, Sunny; Cunningham, Peter; Barnes, Andrew
Highlights: Smokers with symptoms of any mental illness (AMI) are highly dependent on nicotine. Highly dependent smokers face increased difficulty reducing or quitting smoking. We lack evidence about the relationship between AMI, dependence, and cessation. Among 7290 adult smokers, AMI with high dependence predicted lower cessation. Based on our findings this group may require more support to reduce or quit smoking. Abstract: Background: Adult smokers with symptoms of any mental illness (AMI) are highly dependent on nicotine and may face additional difficulty quitting smoking. While there is evidence that adult smokers with AMI have high dependence, there is insufficient evidence regarding the unique role that AMI may play in moderating the relationship between dependence and cessation outcomes over time. Methods: 7290 current established adult smokers at Wave 1 (2013–2014) of the PATH Study also participated in data collection in Waves 2–4 (2014–2018). Linear probability models with individual-level random effects were fit to the data, modeling associations between AMI, nicotine dependence, and the 1) likelihood of achieving cessation during the study period, 2) making a cessation attempt within the previous 12 months, and 3) log of past 30-day total consumption of cigarettes. Results: Adults who experienced both AMI symptoms and high dependence were 4.7 percentage points (PP) less likely to achieve cessation at any point during the study period (p < 0.01) and smoked more cigarettes per month (β = 0.214, p < 0.05) than adults with AMI who were not highly dependent, despite being as likely to attempt to quit. Adults with AMI who were not highly dependent were 4.6 PP more likely to report a quit attempt and 1.6 PP more likely to achieve cessation than those with neither AMI nor high dependence. Conclusions: Adults with AMI are particularly affected by the burden of tobacco use, in part because of the likely interaction between nicotine dependence and AMI. Tobacco control efforts that focus on this interplay may provide an opportunity to better target interventions for this vulnerable population.